2015
DOI: 10.1002/jbm.b.33372
|View full text |Cite
|
Sign up to set email alerts
|

Surface topography, hardness, and frictional properties of GFRP for esthetic orthodontic wires

Abstract: In our previous study, glass-fiber-reinforced plastics (GFRPs) made from polycarbonate and glass fiber for esthetic orthodontic wires were prepared by using pultrusion. The purpose of the present study was to investigate the surface topography, hardness, and frictional properties of GFRPs. To investigate how fiber diameter affects surface properties, GFRP round wires with a diameter of 0.45 mm (0.018 in.) were prepared incorporating either 13 μm (GFRP-13) or 7 μm (GFRP-7) glass fibers. As controls, stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…e previous study confirmed that the GFRTP wires are more transparent than conventional metallic wires [2]. Moreover, field emission scanning electron microscopy and scanning probe microscopy analysis indicated that the surface roughnesses of the GFRTP wires are smoother than those of the β-Ti wire [3]. Furthermore, the GFRTP wires had frictional and flexural properties similar to those of the Ni-Ti wires [2,3].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…e previous study confirmed that the GFRTP wires are more transparent than conventional metallic wires [2]. Moreover, field emission scanning electron microscopy and scanning probe microscopy analysis indicated that the surface roughnesses of the GFRTP wires are smoother than those of the β-Ti wire [3]. Furthermore, the GFRTP wires had frictional and flexural properties similar to those of the Ni-Ti wires [2,3].…”
Section: Introductionmentioning
confidence: 58%
“…In a previous study, esthetic orthodontic wires were produced by pultrusion of GFRTPs composed of a polycarbonate matrix reinforced with E-glass fibers [2,3]. Polycarbonate has been widely used in orthodontic appliances such as esthetic brackets and clear retainers [4], and it was used as a matrix of the GFRTP because of its high transparency, low weight, and high heat resistance [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties and in vitro biocompatibility of GFRP, such as surface characteristics, frictional properties, flexural properties, color stability, and cytotoxicity, were evaluated and we concluded that GFRP wire might be useful in orthodontic treatment (14)(15)(16). To evaluate its potential in clinical orthodontic treatment, we investigated the effects of GFRP wire on orthodontic force and changes in P2W and P3W compared with NiTi wire using an experimental dog model of tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…GFRP straight wire was fabricated using a pultrusion technique described in a previous study (14,15). A polycarbonate (H4000; Mitsubishi Engineering-Plastics Corp., Tokyo, Japan)was used as the thermoplastic matrix because of its low melt viscosity.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation